2021
DOI: 10.1136/bmjopen-2020-047856
|View full text |Cite
|
Sign up to set email alerts
|

Examining LGBTI+ inclusive sexual health education from the perspective of both youth and facilitators: a systematic review

Abstract: ObjectivesTo critically appraise and synthesise the evidence in relation to both the receipt and delivery of LGBTI+ (Lesbian, Gay, Bisexual, Transgender, Intersex) inclusive sexual health education.DesignA systematic review and narrative synthesis.Data sourcesA systematic search of three online databases (EMBASE, PsychINFO and SocINDEX) from January 1990 to May 2021 was conducted.Eligibility criteriaStudies included were (1) peer-reviewed; (2) English; (3) quantitative, qualitative and mixed methods; that eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 44 publications
(101 reference statements)
1
11
0
Order By: Relevance
“…Inclusive curricula seem particularly effective for students who are severely victimized on the basis of gender expression or in schools with hostile climates 33 , 60 . Not all studies found reductions in bullying and victimization after implementing inclusive curricula 31 , 59 .…”
Section: Resultsmentioning
confidence: 99%
“…Inclusive curricula seem particularly effective for students who are severely victimized on the basis of gender expression or in schools with hostile climates 33 , 60 . Not all studies found reductions in bullying and victimization after implementing inclusive curricula 31 , 59 .…”
Section: Resultsmentioning
confidence: 99%
“…47 Furthermore, there are no standardized policies or curricula for delivering sexual health education inclusive of LGB and TGNC students, and many educators feel ill-equipped to provide this education. 48,49 Substantial research is needed to understand the effects of specific curricula, how they are being implemented, and the extent to which use of LGBT-inclusive sexual health curricula directly effects sexual violence and the extent to which the effect is mediated by school climate. Additionally, the finding that an inclusive sexual health curriculum was associated with increased dating violence among heterosexual cisgender students has not been found previously and warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because inclusive curricula increase awareness ,understanding and acceptance (M1), normalise and validate sexual and gender minorities (M2), oppose compulsory heterosexuality (M3), and improve the school climate (M4). 29,31,37,[52][53][54][55][56][57][58][59][60][61][62][63][64]…”
Section: Inclusive Curriculamentioning
confidence: 99%
“…Inclusive curricula seem to be most effective when they: avoid "deficit and at-risk narratives", make the contributions and achievements of LGBTQ+ role models visible, use workbooks and literature that include LGBTQ+ issues, facilitate in-depth reflection on LGBTQ+ topics beyond learning facts, have sticker systems to highlight books with LGBT themes and/or characters, include LGBTQ+ topics in sexual health education, and are implemented from an early age onwards (SAG, YPAG). 37,[52][53][54][55][56][57][58][59] Ideally, inclusive curricula should be co-designed and co-delivered by teachers and LGBTQ+ students (SAG). Our YPAG stated that students should be better educated on the history of LGBTQ+ people, for example the lesbian community providing activism and support during the HIV/AIDS crisis.…”
Section: Additional Information On Mechanisms and Strategiesmentioning
confidence: 99%
See 1 more Smart Citation